Impaired Kallikrein-Kinin System in COVID-19 Patients' Severity - Alfaro, Enrique; Díaz-García, Elena; García-Tovar, Sara; Zamarrón, Ester; Mangas, Alberto; Galera, Raúl; Nanwani-Nanwani, Kapil; Pérez-de-Diego, Rebeca; López-Collazo, Eduardo; García-Río, Francisco; Cubillos-Zapata, Carolina (Frontiers in Immunology, 2022)
COVID-19 has emerged as a devastating disease in the last two years. Many authors appointed to the importance of kallikrein-kinin system (KKS) in COVID-19 pathophysiology as it is involved in inflammation, vascular homeostasis and coagulation. We aim to study the bradykinin cascade and its involvement in COVID-19 patients’ severity. This is an observational cohort study involving 63 consecutive patients with severe COVID-19 pneumonia and 27 healthy subjects as control group. Clinical laboratory findings and plasma protein concentration of KKS peptides (bradykinin (BK), BK1-8), KKS proteins (high-molecular-weight kininogen (HK)) and KKS enzymes (carboxypeptidase N subunit 1 (CPN1), kallikrein B1 (KLKB1), angiotensin converting enzyme 2 (ACE2), C1 esterase inhibitor (C1INH)) were analyzed. We detected dysregulated KKS in COVID-19 patients, characterized by an accumulation of BK1-8 in combination with decreased levels of BK. Accumulated BK1-8 was related to COVID-19 patients’ severity. A multivariate logistic regression model retained BK1-8, BK and D-dimer as independent predictor factors to ICU admission. A Youden’s optimal cut-off value of 0.352 was found for the multivariate model score with an accuracy of 92.9%. Multivariate model score-high group presented an odds ratio for intensive care unit (ICU) admission of 260.0. BK1-8 was related to inflammation, coagulation and lymphopenia. Our data suggest BK1-8/BK plasma concentration in combination with D-dimer levels might be retained as independent predictors for ICU admission in COVID-19 patients. Moreover, we reported kallikrein-kinin system dysregulation in COVID-19 patients which was related to disease severity by means of inflammation, hypercoagulation and lymphopenia